VISUALISASI MITOS DEWI SRI DALAM SENI LUKIS - Gigih Wiyono (SURYA SENI, 2008)
The Myth of Devi Sri in Painting. Most Javanese, Balinese, Kalimantanese and people in other areas believe that Dewi Sri is the goddess of rice and fertility. Earth is the place where Dewi Sri’s soul lives and resides. No other goddess the farmers adore and love like Dewi Sri who is also Nyi Pohaci asthe farmers’ mother. Soil is often disturbed by the power that will facilitate her existence. In Java, the violence against the earth is told in Dewi Sri fairy tale. In many mythologies woman is described as the fertility symbol. Dewi Sri’s death is like Jesus’ death, her death enlivens. Dewi Sri’s death gives the farmers life-energy. Coconut tree emerges from her head, rice plant grows from her navel, sugar palm tree grows from her vagina and papaya tree grows from her breast. Mango tree grows from her hands and edible tuber and cassava grow from her feet.Visualization of Dewi Sri Myth in the art of painting is a concept of representing the myth of Dewi Sri . Based on the creative idea and perspective, the writer tries to treat, to transform the ﬁgure of Dewi Sri Myth in the current context. In this concept, Dewi Sri is represented through the painting using impasto,underpainting and rendering techniques. Here Dewi Sri is presented symbolically so that the visualization emerging can remain to be perceived as work representing its age.Visualization of Dewi Sri’s symbols is the manifestation of the author in two-dimensional work through canvas, wood, and oil paint media with pallet knife and brushes, and other mixed media material to give new motif and colour in the art world, particularly in the creation of painting.Keywords: Dewi Sri and myth